2017
DOI: 10.31219/osf.io/gq8hx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fundamental role of Warburg effect in various pathophysiological processes

Abstract: Even though high NO via iNOS was involved in most of the pathologies including sepsis, any 56 substance that inhibits or uncouples the mitochondrial respiration can initiate this Warburg effect 57 and irreversible dedifferentiation. A mild and reversible Warburg differentiation dedifferentiation 58 effect may be necessary for normal functioning and the same effect in exaggerated and irreversible 59 way leading to irreversible dedifferentiation states may be the underlying mechanism in most of the 60 diseases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 162 publications
(241 reference statements)
0
1
0
Order By: Relevance
“…Recent studies showed that the Warburg effect occurs not only cancers but also in inflammatory and sepsis conditions. [12,13] I speculate that the Warburg effect occurs in COVID-19 in various organs especially in the lungs, the main organ affected by SARS-CoV-2. 1) It is well known that hypoxia-inducible factor 1 alpha (HIF-1α) is known to activate glycolytic enzymes and produce Warburg effect.…”
Section: Does the Warburg Effect Occur In Covid-19?mentioning
confidence: 99%
“…Recent studies showed that the Warburg effect occurs not only cancers but also in inflammatory and sepsis conditions. [12,13] I speculate that the Warburg effect occurs in COVID-19 in various organs especially in the lungs, the main organ affected by SARS-CoV-2. 1) It is well known that hypoxia-inducible factor 1 alpha (HIF-1α) is known to activate glycolytic enzymes and produce Warburg effect.…”
Section: Does the Warburg Effect Occur In Covid-19?mentioning
confidence: 99%